2022
DOI: 10.3390/genes13030519
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Reveals Differentially Expressed Genes Associated with High Fiber Quality in Abaca (Musa textilis Nee)

Abstract: Despite the importance of and current demand for abaca (Musa textilis Nee) fiber, there has been limited study that capitalizes on RNA-seq to identify candidate genes associated with high fiber quality and bunchy top virus (AbBTV) resistance. Three varieties (Abuab, Inosa, and Tangongon), one wild banana variety (Musa balbisiana Colla) Pacol, and two developed backcrosses (Abuab × Pacol BC2 and BC3) were grown at the Institute of Plant Breeding (IPB), Laguna, Philippines. The pseudostems of 3-month-old suckers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Based on initial field assessment, it has superior fiber quality and is resistant against bunchy top virus. Molecular study using RNA-seq revealed that it is the best among five abaca genotypes as it induces significantly higher number of genes associated with both desirable traits [16].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on initial field assessment, it has superior fiber quality and is resistant against bunchy top virus. Molecular study using RNA-seq revealed that it is the best among five abaca genotypes as it induces significantly higher number of genes associated with both desirable traits [16].…”
Section: Resultsmentioning
confidence: 99%
“…Only features with total normalized read count of 20 reads between the two specific alleles were considered for further analysis (AbuabBC2 + PacolBC2 ≥ 20; AbuabBC3 + PacolBC3 ≥ 20) to ensure genes are expressed and to avoid inclusion of artifacts, as previously performed (e.g. [12,16,37,38]. We incremented read counts with a value of 1 for genotype-specific alleles with 0 read counts to avoid a numerator or a denominator of 0.…”
Section: Allelic Imbalance Polymorphism In the Backcrossesmentioning
confidence: 99%
See 3 more Smart Citations